The Role of Basic Psychological Needs Satisfaction in Finnish Vocational Students' School Burnout and Dropout Intentions - Pylväs, Laura; Nokelainen, Petri (International journal for research in vocational education and training, 2025)
Purpose: This study examined how vocational education and training (VET) students' satisfaction of basic psychological needs in VET learning environments, namely autonomy, competence, and relatedness, is related to their burnout and intention to leave VET. Self- Determination Theory was employed in the study. The aim of the study was to contribute to the existing body of empirical knowledge on basic psychological needs in educational contexts, with a particular focus on their role in negative processes. The findings may assist in evaluating the potential of basic psychological needs support in enhancing student motivation and well-being in VET learning environments.  Methods: Cross-sectional online survey data were collected in 2023 from 255 students at a large vocational institution in Finland. The questionnaire included the following factors from three validated scales: Basic Psychological Need Satisfaction - Work Domain (BPNS-WD; "autonomy", "competence", "relatedness"), School Burnout Inventory (SBI; "exhaustion", "cynicism"), and dropout intentions. Data were analysed in R using correlation analysis, confirmatory factor analysis, and structural equation modeling.  Results: The results indicated that the factors of basic psychological needs were negatively associated with the two burnout factors and the factor of dropout intentions, confirming our hypotheses. However, the hypotheses were only partially confirmed as not all associations reached statistical significance. Contrary to our hypothesis, relatedness satisfaction was positively related to burnout cynicism, although the relationship was not statistically significant.  Conclusions: The findings suggest that supporting the basic psychological needs of VET students may reduce school burnout and the intention to drop out of school. Nevertheless, further research is required at the institutional and workplace levels to investigate the potential influence of perceived social relatedness on the development of burnout cynicism, and vice versa. Furthermore, the results indicated that female students, as well as those with older age or less work experience, experienced more burnout exhaustion than other respondents. A more comprehensive analysis is needed to gain better understanding of the factors that increase exhaustion within these groups of students.